Factors Influencing Work Retention of Professional Nurse under the Ministry of Public Health - กระเทศ จุฬาพร; พัฒนะวาณิชนันท์ ณัฏฐญา; ประทานวรปัญญา วรารัตน์; ไตรนาทถวัลย์ วินัย; ถ่างกระโทก ปราโมทย์; ศรีทุมสุข วีรยุทธ (Journal of Health Science of Thailand, 2021)
This research aimed to explore the predictive factors that associated the happiness of nursing practice, work-life balance, and organizational commitment with the retention of registered nurses in the Ministry of Public Health. The participants were 82,205 registered nurses, both females and males, who worked in the hospitals under Ministry of Public Health. Data were collected online by using the following questionnaires: (1) happinometer, the tool for happiness assessment of the Ministry of Public Health’s personnel (happinometer); (2) work-life balance assessment; (3)organization commitment assessment; (4) work retention assessment. Descriptive statistics, one-way ANOVA, Pearson’s correlation coefficient, and path analysis were used for data analysis. It was found that happiness of nursing practice and work-life balance had a direct effect on organizational commitment (path coefficients = 0.50 and 0.78, respectively). The organization’s commitment also showed direct effects on the retention of registered nurses (path coefficients = 0.78). Conversely, the work retention was direct effects to organization commitment (path coefficients = 0.26) (c2 = 780.71, p-value<0.001, RMSEA = 0.096). However, happiness of nursing practice and work-life balance had no direct effect on work retention of registered nurses. Analysis of the total effect by path analysis revealed that happiness of nursing practice, work-life balance, and organizational commitment could predicte 75 percent of work retention of registered nurses. Therefore, happiness of nursing practice, work-life balance, and organizational commitment were factors significantly associated with work retention of registered nurses in the Ministry of Public Health. Thus, policies and programs to promote happiness, organization commitment and work-life balance should be developed in order to retain registered nurses in the health system.